Assessing the Information and Communication Technology Proficiency of the BSOA Students, Philippines: Gateway to Employee-Ready Graduates - Taller, Magdaline M.; Siguenza, Leizel; Tayag, Cyrille Kaye D. (Journal of Organizational and Human Resource Development Strategies, 2024)
This paper aimed to assess the level of Information and Communication Technology Proficiency among BSOA students, as well as the potential barriers that affected their ICT skills, including hardware operations, software processing, information management, digital communication, and data security and privacy. Additionally, it proposed an intervention program to enhance the Information and Communication Technology proficiency of BSOA students. One hundred twelve (112) 2nd to 4th-year students enrolled in the Bachelor of Science in Office Administration (BSOA) program at Camarines Sur Polytechnic Colleges - Buhi Campus were systematically chosen to serve as the respondents. The Descriptive Method was used to attain the objectives. The instrument used in this study was a research-made survey questionnaire for data collection and was interpreted using a weighted mean. The findings revealed that BSOA students' ICT proficiency demonstrates a mixed landscape and exhibits a consistent trend of moderate proficiency in ICT aspects, specifically in hardware operations, software processing, information management, digital communication, and data security and privacy.